The Tudors. The complete first season [videorecording (DVD)] - Rawi, Ousama, 1939-; Hirst, Michael, 1952-; Rhys-Meyers, Jonathan, 1977-; Neill, Sam; Blue, Callum, 1977-; Cavill, Henry, 1983-; Czerny, Henry; Frain, James; Northam, Jeremy, 1961- (Showtime Entertainment ; CBS DVD : Distributed by Paramount Home Entertainment, 2008)
A look at the early life of King Henry VIII, beginning after his assumption of the British throne at the age of 19.